2013
DOI: 10.3109/02699052.2013.831131
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after traumatic brain injury: Systematic review

Abstract: The main outcome measures were employment status and return to work after TBI. Methodological quality of most of the relevant 12 controlled and 68 uncontrolled studies included in the review was estimated as very low. There was weak evidence that age, educational level, pre- and post-injury occupational status, severity of TBI, functional status, level of depression and anxiety, gender and race may be predictive for the vocational outcome after TBI. CONCLUSIONS AND IMPLICATIONS FOR FURTHER RESEARCH: No strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 94 publications
4
86
0
2
Order By: Relevance
“…The quotes show participants' adjustment to their deficits in terms of making adaptations to their lives and relationships. Employment was shown to be an important marker of improvement, which is supported by research showing this to be a common goal of rehabilitation (Saltychev, Eskola, Tenovuo, & Laimi, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…The quotes show participants' adjustment to their deficits in terms of making adaptations to their lives and relationships. Employment was shown to be an important marker of improvement, which is supported by research showing this to be a common goal of rehabilitation (Saltychev, Eskola, Tenovuo, & Laimi, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…These findings are supported by the results from Willmott et al (30), who reported that a return to study after a TBI was limited by fatigue and required reduced study hours and a need for far greater effort. It has been difficult to find predictors for the failure or success of a return to work after TBI (31,32). However, depression and anxiety measured with the Hospital Anxiety and Depression Scale (HADS) (33) and the subscales cognition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Matuseviciene et al tried to avoid this confound by offering an early intervention visit by a rehabilitation specialist compared to providing written information to estimated high-risk patients with three or more PCS after MTBI, but their studies showed no difference in return-to-work (RTW) between interventions [14]. Participation such as RTW is an important goal in rehabilitation because being unemployed affects various dimensions of physical, psychological and social health [15]. RTW has been stated to be a good indicator of patient well-being and adaption after MTBI [16].…”
Section: Introductionmentioning
confidence: 99%